PREVALENCE OF HBsAg IN ADULTS NEEDING ENDOSCOPY AND ITS LIKELY AETIOLOGICAL FACTORS - Manan, Alamzeb (Journal of Ayub Medical College Abbottabad, 1998)
A total of 1200 patients needing endoscopy for upper and lower Gastrointestinal symptoms were screened for HBsAg at the DHQ Teaching Hospital of Ayub Medical College Abbottabad, using the Hepatitis-B Quick Test of the 1200 patients 553 were females and 647 males. Amongst these 40(3.33 %) were HBsAg positive, of which 16 were male and 24 females. 33(82%) patients gave a history of parenteral injection; 24(60%) of I/V infusion and 5(12.2%) had no history of injections /infusion or transfusion. The above figures suggest that HBsAg is not as common in Hazara as compared to studies done in bigger towns of Pakistan secondly parenteral therapy seems to be the most important mode of transmission. In order to further reduce the incidence, we need to educate the people the paramedical staff and laboratories dealing blood transfusions.